Vorläufiger Bericht über den Zuckerrohranbau in Andalusien und in Louisiana - Blume, Helmut (ERDKUNDE, 1955)
In this article an agricultural-geographical comparison of the Costa del Sol and Louisiana is carried out from the point of view that, in both areas, though situated at the climatic margin of sugar cane, the cultivation of this crop dominates. As a result of different climatic conditions the methods of cultivation in these two sub-tropical areas differ considerably. Although the Costa del Sol lies about 650 km. further north than the Sugar Bowl of Louisiana, cultivation in Andalusia, in contrast to that of Louisiana, can be carried on in a way which in certain aspects resembles that of the tropical areas where sugar cane is grown. The reason for this is the sheltered position of the Costa del Sol due to the protection afforded by the Betic Cordillera. Strong advances of cold air such as those which reach the delta of the Mississippi without obstacle are unknown on the Andalusian coast. The most remarkable phenomenon at the Costa del Sol is the fact that when the crop is changed after a field has been under sugar cane for five years, in some vegas it is followed by sugar beet.